Manifestation of a probable lethal gene in Holstein Friesian cows - Pinheiro, L. E L [UNESP]; Andrade, A. M L [UNESP] (Elsevier, 1985)
In a study of the causes of abortion and stillbirth in a Holstein-Friesian herd, the most probable cause detected was a lethal gene transmitted through the pedigree line. Findings of this nature have already been reported both in the United States and Canada for the same line. Replacing the sires with others solved the problem, thus demonstrating a genetic etiology for abortion and stillbirth in this lineage. The differences noted in the time of fetal mortality may indicate the action of more than one gene or variable expressivity of the mutant gene. The importance of the data is discussed in terms of the elimination of genetic factors that cause fetal mortality. © 1985.
Keywords: abortion; cattle; inbreeding; lethal gene; stillbirth